Decision Making Behavior in Seeking Help and Utilizing Health Services in Maternal Death Cases in Berau Regency: Application of Andersen's Behavior Model and Pass Model - Heni Sudiastiningsih; Iwan Muhammad Ramdan; Annisa Nurrahmawati; Nur Rohmah; Jasmawati Jasmawati; Dini Indo Virawati; Ratna Wati; Muhammad Arifin (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
One of the causes of the high maternal mortality rate is the delay in seeking help. Delays in seeking help will have an impact on further delays, namely delays in utilizing health facilities which result in delays in receiving appropriate and adequate services. This study is a qualitative research with a phenomenological approach by collecting data through in-depth interviews with families of cases of maternal death in Berau with the aim of exploring the family's experience in the process of seeking health help by utilizing health services for pregnant women. The results showed that social support was related to family demographics with treatment practices still found based on local tribal customs. Perceived severity and vulnerability motivated families to seek health care. Trust in the ability of health workers also plays a role in the utilization of health facilities. This study provides information for families of pregnant women, communities and policy makers in designing more effective health programs, especially increasing knowledge related to maternal health. Improving the professionalism and competence of health workers as an attraction for the community to choose health services as the first choice when they need help Keyword: Maternal mortality;health seeking behavior ;health care utilization